Effects of the radiative recombination on the intensity and polarization of the Ly-α emission of hydrogen-like ions - Bettadj, L.; Inal, M. K.; Surzhykov, Andrey; Fritzsche, Stephan (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 2010)
The intensity ratio of the Ly-α1(2p3/2→1s1/2) to Ly-α2(2p1/2→1s1/2) photon emission is analyzed for hydrogen-like Fe25+ ions if their excitation arises in a plasma not only from the electron impact but also due to the radiative recombination (RR) of initially bare Fe26+ ions. Under such conditions, the intensity ratio and the (degree of) linear polarization of the Ly-α1 line are explored for collisions with an electron beam over a wide range of kinetic energies up to 50keV. Apart from the direct population of the 2p1/2,3/2 levels via the RR of bare ions, the contributions from radiative cascades and higher multipoles are taken into account by applying a fully relativistic theory for the motion of the electrons and the electron-photon coupling. Our calculations show an overall small effect of the RR upon the degree of the Ly-α1 polarization as well as the Ly-α1/Ly-α2 intensity ratio under usual plasma conditions. However, the effects from the RR of initially bare ions may become significant at electron beam energies ∼7-10keV, for plasma conditions far away from ionization equilibrium with a relatively large proportion of bare Fe ions, as it may be realized in electron-beam ion trap experiments.